1975
DOI: 10.1002/bjs.1800620118
|View full text |Cite
|
Sign up to set email alerts
|

Secondary involvement of the penis by rectal cancer

Abstract: Two cases of metastasis to the penis from a primary rectal carcinoma are described. The clinical features, treatment and prognosis together with the probable modes of metastasis are discussed. All previously reported cases of penile metastasis from the rectum are reviewed. It is suggested that contrary to previous reports that prognosis is not uniformly poor and hence a more aggressive attitude to treatment should be adopted. Metastatic lesions in the penis should also be considered as a cause of urinary obstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Despite its rich vascular supply and its proximity to the rectum, bladder, and prostate, which are common sites of malignancy, metastatic involvement of the penis is rare [3]. In our review, we found that penile metastases from rectal cancer usually present on average 37 months after the treatment of the primary tumour.…”
Section: Discussionmentioning
confidence: 91%
“…Despite its rich vascular supply and its proximity to the rectum, bladder, and prostate, which are common sites of malignancy, metastatic involvement of the penis is rare [3]. In our review, we found that penile metastases from rectal cancer usually present on average 37 months after the treatment of the primary tumour.…”
Section: Discussionmentioning
confidence: 91%
“…7 Penile metastases usually present on average 13 months after diagnosis of primary tumor and two-thirds have disseminated metastases at presentation. 1,2 The most common presenting symptoms in order are difficulty voiding, perineal pain, asymptomatic nodule and priapism.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sufficient blood flow of the penis is ensured by an abundant amount of vascular structures ( 71 ). However, despite these factors, metastatic involvement of the penis is extremely rare ( 14 , 65 , 72 , 73 ). So far, only 72 cases have been described in the literature ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%